A case of corticobasal degeneration that progressed from primary progressive aphasia - Shoji, Mikio; Kawarabayashi, Takeshi; Nagano, Isao; Matsubara, Etsuro; Abe, Koji (Nihon Rōnen Igakkai zasshi, 2005)
A 65-year-old woman began to experience slowly progressive speech disturbance from 2001. She was admitted to our hospital for examination on May 2003. She had dysprosody, paragraphia, and mild disturbance in comprehension of spoken language. Repetition was preserved. No clear paraphasia was found. Calculation was disturbed, but there were no other neurological abnormalities including apraxia and agnosia. Brain MRI showed atrophy of the left frontal and parietal lobes. 99mTc-ECD SPECT showed decreased blood flow in the left frontal lobe and parietal lobe, especially in the Broca area and supplemental motor cortex. Primary progressive aphasia was diagnosed, because aphasia lasted for 2 years without other neurological deficits, and her daily activity was well preserved. During follow up, facial apraxia appeared from December 2003, and limb apraxia appeared from May 2004, followed by rigidity predominantly in the right upper limb and dementia. She was diagnosed as having corticobasal degeneration (CBD). The second SPECT on December 2004 showed progression of the decrease in cerebral flow at the same area showed by the first SPECT. SPECT is useful examination to predict the progress of the disease because the decrease of blood flow was recognized before the progression to CBD.